Sustainability Issues of Aqua Tourism in Kerala - Akash, J H; Aram, I Arul (Atna Journal of Tourism Studies, 2018)
Tourism is interlinked with the natural environment and generates a lot of employment opportunities. The rapid growth of tourism industries has led to the destruction of nature because in most cases, tourism industry concentrates only on economic viability. The development of the tourism industry should balance with ecology, society, culture, and economy for their sustainability. The quality of nature is essential for tourism. The negative impact of tourism development can gradually destroy natural environmental resources on which it depends. In this paper, the authors describe the effects of tourism on natural resources, environmental pollution, and recent issues associated with Kerala tourism with specific reference of coastal areas.